EFFECT OF SOWING TIMING ON SOYBEAN YIELD (Multidisciplinary Journal of Science and Technology, 2026)
Choosing the optimal sowing dates for soybean seeds is of great importance for obtaining high grain yields. The study examined the influence of sowing dates and application of bentonite clay along with mineral fertilizers on soybean yield. Soybean seeds were sown on March 20-25, April 5-10, and April 20-25. Bentonite clay was applied during the soybean growth period along with mineral fertilizers at a rate of 250 kg/ha during the branching stage, 250 kg/ha during the flowering stage, and 250 kg/ha at the beginning of the pod formation stage, totaling 750 kg/ha. Field germination of seeds in the variant sown on March 20-25 was 85.3%, while in the variant sown on April 20-25 it was 78.3%. Field germination in the variant sown on April 5-10 was 87.2%, and a high yield indicator was also noted, with a grain yield of 26.3 centners/ha obtained. When bentonite clay was applied, an additional grain yield of 4.7 centners/ha (15%) was obtained.